2018
DOI: 10.1007/978-1-4939-8648-4_21
|View full text |Cite
|
Sign up to set email alerts
|

Fc Engineering: Tailored Synthetic Human IgG1-Fc Repertoire for High-Affinity Interaction with FcRn at pH 6.0

Abstract: The therapeutic efficacy of an antibody drug depends on the variable domains and on the constant crystallizable fragment (Fc). IgG variable domains have been the targets of extensive molecular engineering in search of more specific binders with higher affinities for their targets. Similarly, Fc engineering approaches have led to modulating both the immune effector responses and serum half-lives of therapeutic antibodies. A high-affinity interaction between the IgG Fc and neonatal Fc receptor (FcRn) at a slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The overall stoichiometry arrangement of Fc-FcRn complexes was found to be similar in both rodents and humans, 8,10,11 where studies revealed the involvement of the FcRn a1-a2 domain platform interacting with the Fc CH 2 -CH 3 domain interface loops. Engineering studies on IgG1 for FcRn have also been reported, [12][13][14][15][16][17][18] with one of the most noteworthy Fc variant, the IgG1 Fc YTE mutant (Met252Tyr, Ser254Thr and Thr256Glu mutations). The IgG1 Fc YTE mutant was reported to show $10-fold improved pH-dependent binding affinity whilst exhibiting $2 to 4-fold prolonged serum half-life in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall stoichiometry arrangement of Fc-FcRn complexes was found to be similar in both rodents and humans, 8,10,11 where studies revealed the involvement of the FcRn a1-a2 domain platform interacting with the Fc CH 2 -CH 3 domain interface loops. Engineering studies on IgG1 for FcRn have also been reported, [12][13][14][15][16][17][18] with one of the most noteworthy Fc variant, the IgG1 Fc YTE mutant (Met252Tyr, Ser254Thr and Thr256Glu mutations). The IgG1 Fc YTE mutant was reported to show $10-fold improved pH-dependent binding affinity whilst exhibiting $2 to 4-fold prolonged serum half-life in humans.…”
Section: Introductionmentioning
confidence: 99%
“…14 Oen, the effects of the solvent environment such as pH are key factors in biochemical reactions, including the Fc-FcRn binding mechanism. 5,11,15,19 Although conventional molecular dynamics (MD) simulation has prompted molecular discovery in biological studies, system settings with a xed protonation state for solute titratable residues throughout the simulation may hinder the visualization of complex conformational changes in different pH environments. Thus, an auxiliary for MD simulation, constant pH molecular dynamics (CpHMD) simulation, which allows dynamic changes in the protonation states of titratable residues based on changes in the environmental pH was applied in this study.…”
Section: Introductionmentioning
confidence: 99%